Mycobacterium shimoidei, a Rare Pulmonary Pathogen, Queensland, Australia - Timothy M. Baird; Robyn Carter; Geoffrey Eather; Rachel Thomson (Emerging Infectious Diseases, 2017)
Nontuberculous mycobacteria are human pathogens with increasing incidence and prevalence worldwide. Mycobacterium shimoidei is a rare cause of pulmonary disease, with only 15 cases previously reported. This series documents an additional 23 cases of M. shimoidei from Queensland, Australia, and highlights the pathogenicity and clinical role of this species.